Early Dilmun Burial Mounds in Bahrain: the Wâdî al-Sail Archaeological Project and the Dilmun Mapping Project - Masashi Abe; Akinori Uesugi (Arabian Humanities)
This paper overviews the results of archaeological research by the Japanese mission on the Early Dilmun burial mound sites. The archaeological research on Early Dilmun burial mounds in Bahrain has a history of more than 100 years. Excavations of a number of burial mounds, including 'Royal Mounds', have revealed different aspects of the mortuary and burial practice of the Early Dilmun period and the emergence of a complex society on Bahrain Island. However, there are many issues to be discussed with different approaches; how the mortuary practices changed through time, how the distribution pattern of burial mounds changed through time, how the social organization can be approached from burial mounds, and so on. The Dilmun Mapping Project run by Akinori Uesugi, one of the authors of this paper, focuses on the distribution pattern of burial mounds and the formation process of extensive cemeteries. The Wâdî Al-Sail Archaeological Project led by Masashi Abe has been revealing the mortuary and burial practice of the Early phase of the Early Dilmun period, which was not so well understood before. In addition, Wâdî Al-Sail provides an important clue for considering the origins of Dilmun.